Methane combustion in MILD oxyfuel regime: influences of dilution atmosphere in co-flow configuration - Chen, Sheng; Liu, Hao; Zheng, Chuguang (Elsevier, 2017)
MILD (moderate or intense low oxygen dilution) oxyfuel combustion is a recently proposed clean combustion mode which can remedy the shortcomings of the standard oxyfuel combustion technology. Nowadays most available studies on MILD oxyfuel combustion focus on how to realize this new combustion regime in O2/CO2 atmosphere. The open research on methane MILD oxyfuel combustion in O2/H2O atmosphere is quite sparse. In the present work, we carry out a comprehensive comparison study on methane MILD oxyfuel combustion in different dilution atmosphere for the first time. The JHC (jet in hot co-flow) burner is adopted as a research prototype. The investigation is based on numerical simulation, so firstly the adopted numerical approach is validated by some experimental data in open literature. The numerical comparison is conducted by varying the mass fraction of oxygen in the co-flow and the temperature of the hot co-flow, two key parameters affecting fine reaction structures in JHC. Through the present investigation, a number of findings are reported for the first time and some conclusions presented in previous publications are checked with analyses, especially on some conflicted claims between the previous publications. In addition, several new questions are raised, which may inspire further research activities in future.